Determining drivers of dragonfly diversity patterns and the implications for conservation in South Africa. (May 2020) - Deacon, Charl; Samways, Michael J.; Pryke, James S.
Abstract: Knowing where species occur is essential for conservation planning. In South Africa, regional climatic variation is subject to effects of oceanic current systems, which in turn, determine species diversity patterns. We hypothesize that regional climates and topography are important drivers of aquatic insect species richness, endemism, and assemblage composition, and expect strong assemblage-turnover boundaries to be concurrent with topographical features. We also expected that current conservation networks do not represent aquatic insect species richness and endemism. We used generalized linear mixed models and generalized dissimilarity models to determine drivers of South African dragonfly (Odonata) species richness and assemblage-turnover, as well as to investigate the extent of assemblage-turnover boundaries. We found that climate gradients were significant drivers, and found significant variation in assemblages between sub-regions. Turnover boundaries were gradual but concurrent with topographical features and/or areas with spatial changes in sub-regional climate. Modern-day climate and topography partially explained dragonfly diversity patterns, but other local factors and past geological events likely both contribute to current dragonfly diversity patterns. The existing conservation network in South Africa represents areas of high dragonfly species richness and endemism. We recommend additional conservation efforts in areas outside of protected areas with high species richness and endemism levels, but importantly also in areas with high assemblage-turnover rates to ensure protection of as many species as possible. We also propose further searches in areas with high endemism and high assemblage-turnover for possible discovery of unknown species, and further searches in under-represented areas to improve distribution data for known species. Highlights: Climate gradients drive the rich South African dragonfly fauna. Assemblage composition varies substantially across the region. Assemblage-turnover boundaries are gradual at the regional scale. Turnover boundaries are determined by topography and spatial climatic variation. The conservation network of South Africa represents dragonflies well.